On the Core of Double Sequences - Sever, Yurdal; Altay, Bilal (Sarajevo Journal of Mathematics, 2024)
In this paper, we define the core of double sequences via barriers and disks. We show that these definitions are equivalent and give an inequality related to the P-core of bounded double sequences. 2010 Mathematics Subject Classification. 40B05, 40C05.